Ekstrak Air Tapak Dara Menurunkan Kadar Gula dan Meningkatkan Jumlah Sel Beta Pankreas Kelinci Hiperglikemia (THE WATER EXTRACT OF TAPAK DARA DECREASES BLOOD GLUCOSE CONCENTRATION AND INCREASES INSULIN PRODUCTION BY PANCREATIC BETA-CELLS ON HYPERGLYCEMIC - Widyastuti, Srikayati; Suarsana, I Nyoman (Jurnal Veteriner, 2012)
The present study was carried out to investigate the effects of tapak dara (Catharanthus roseus) onblood glucose level and insulin profile in hyperglicemic rabbits. Fifeteen local male rabbits were used forthis study. The rabbits were randomly divided into five groups. Group 1 (K-), a control negative group;group 2 (K+), a control positive hipergliccemia; group 3 (KT1) and group 4 (KT2), were groups hiperglicemiaand treated with water extract of tapak dara doses 1 and 2 g/kg bw, respectively; and group 5 (KO), a grouphiperglicemia that treated with glibenclamide 2 mg/kg bw. The result showed water extract of tapak daradose 1 g/kgbw could not decrease the blood glucose level in hyperglycemic rabbits, while dose 2 g/kg bwcould decline blood glucose level in rabbits. This decline had no significantly difference compared withglibenclamide treatment (P> 0.05). Immunohistchemistry result indicated that water extract of tapakdara could stimulate beta cells pancreas to produce insulin.
Keywords: blood glucose, insulin, rabbit, tapak dara (Catharanthus roseus)